Analisis Pengelolaan Wakaf Uang pada Koperasi Simpan Pinjam Pembiayaan Syariah (KSPPS) Gumarang Akbar Syariah Mataram - Rani Lestari; Muhamad Yusup; Pongky Arie Wijaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Gumarang Akbar Syariah Mataram Savings and Loans Cooperative (KSPPS) is an institution that manages zakat and waqf funds for the welfare of the people. This study aims to determine the process of cash waqf management and to determine the effectiveness of cash waqf management at KSPPS Gumarang Akbar Syariah Mataram. The type of research used is qualitative with a descriptive approach and the data collection techniques used are observation, interviews and documentation. The results of this study indicate that the waqf implemented by KSPPS Gumarang Akbar Syariah Mataram is in the form of cash waqf. In collecting waqf funds, the proceeds from collecting waqf money are used for empowerment/economic welfare of the people and for social-religious activities. And the management of cash waqf carried out by KSPPS Gumarang Akbar Syariah Mataram has not been implemented effectively because the funds managed are still very minimal. And if seen from the regulations BWI Regulation Number 1 of 2009 concerning guidelines for the management and development of movable waqf assets in the form of money, they are still carried out in a simple manner or have not been implemented in accordance with these guidelines.